Effects of Cluster Training on Muscle Hypertrophy: A Systematic Review - Alarcón-Rivera, Miguel (2024)
Objective: The aim of this systematic review was to determine the effects of cluster training on musclehypertrophy.Methodology: A literature search was performed in the electronic databases Pubmed, Scopus and Web of Science,using the following keywords: “cluster training”, “rest interval”, “rest pause”, “hypertrophy”, “resistance training”and “cross sectional area”. We included clinical trials that used cluster training as an intervention in people over 18years of age of both sexes.Results: The systematic review obtained during the search of the databases consulted yielded a total of 23 potentially eligible articles, of which a sample of 9 was taken from which results could be obtained that responded to the objective of this review. The number of participants from the 9 eligible articles was 172 subjects. Cluster workouts allow for increased training volume and intensity without causing high levels of fatigue, thus favoring the development of musclehypertrophy.Conclusions: The results of this systematic review suggest that cluster training can be an effective tool for the development of muscle hypertrophy.